Shahzada Saif ul Mulook - Kardar, Iqbal; Ferozsons Pvt Ltd (Lahore Ferozsons Pvt Ltd)
The epic tale of Shahzada Saif-ul-Malook tells the story of an Egyptian prince who falls in love with a fairy, Badi-ul-Jamal, after seeing her in a dream. The prince embarks on a spiritual journey to find her, facing challenges and ultimately experiencing a transformation from a worldly prince to someone with a deeper, more spiritual understanding.
Keywords: Urdu fiction